Effective Recognition of Lithium Salt in (Choline Chloride: Glycerol) Deep Eutectic Solvent by Reichardt’s Betaine Dye 33 - Manish Kumar; Abhishek Kumar; Siddharth Pandey (Liquids, 2023)
Deep eutectic solvents (DESs) have emerged as novel alternatives to common solvents and VOCs. Their employment as electrolytes in batteries has been an area of intense research. In this context, understanding changes in the physicochemical properties of DESs in the presence of Li salts becomes of utmost importance. Solvatochromic probes have the potential to gauge such changes. It is reported herein that one such UV–vis molecular absorbance probe, Reichardt’s betaine dye 33, effectively manifests changes taking place in a DES Glyceline composed of H-bond accepting salt choline chloride and H-bond donor glycerol in a 1:2 molar ratio, as salt LiCl is added. The lowest energy intramolecular charge–transfer absorbance band of this dye exhibits a 17 nm hypsochromic shift as up to 3.0 molal LiCl is added to Glyceline. The estimated <semantics><msubsup>ETN</msubsup></semantics> parameter shows a linear increase with the LiCl mole fraction. Spectroscopic responses of betaine dye 33, N,N-diethyl-4-nitroaniline and 4-nitroaniline are used to assess empirical Kamlet–Taft parameters of dipolarity/polarizability (<semantics>π*</semantics>), H-bond-donating acidity (α) and H-bond-accepting basicity (<semantics>β</semantics>) as a function of LiCl concentration in Glyceline. LiCl addition to Glyceline results in an increase in α and no change in <semantics>π*</semantics> and <semantics>β</semantics>. It is proposed that the added lithium interacts with the oxygen of the –OH functionalities on the glycerol rendering of the solvent with increased H-bond-donating acidity. It is observed that pyrene, a popular fluorescence probe of solvent polarity, does respond to the addition of LiCl to Glyceline, however, the change in pyrene response starts to become noticeable only at higher LiCl concentrations (<semantics>mLiCl</semantics> ≥ 1.5 m). Reichardt’s betaine dye is found to be highly sensitive and versatile in gauging the physicochemical properties of DESs in the presence of LiCl.